Gemcitabine and vinorelbine: treatment option in recurrent platinum – resistant ovarian cancer - Sharaf Eldeen, Doaa Ali Mohammad; Abdelgawad, Abdelgawad Elmetwaly (European Journal of Oncology and Environmental Health, 2018)
Background and aim of the work: to evaluate the efficacy and toxicity of vinorelbine plus gemcitabine combination in patients who had recurrent platinum resistant ovarian cancer. Patients and method: twenty one patients with recurrent platinum resistant ovarian cancer were designated to receive vinorelbine 25 mg/m2 plus gemcitabine 1 gm/m2 on 1st and 8th day of each 21 – day cycle. Results: The Median age was 56 years (range 38-67). One patient (4.8%) achieved complete response and 5 patients (23.8%) had partial response with an overall response rate 28.57%. Median time to progression was 4 months and median overall survival was 11 months. Toxicity was modest and generally tolerated. Nine events (42.85%) of grade 3 hematological toxicity and only one event (4.57%) grade 3 non hematologic toxicity were observed. Conclusion: The combination of gemcitabine and vinorelbine is a moderately active regimen in recurrent platinum resistant ovarian cancer with  an acceptable toxicity  rating it as  an option in treatment of such disease.